Groundwater abstraction through river-bed collector well: A case study based on geophysical and hydrological investigation - Banerjee G. (My University, 2025)
Owing to lack of rational basis, design of radial collector (RC) well often becomes a confusing task for the designers arising out of a wide difference between the anticipated yield and the observed yield from RC wells. In this study, a long-term pumping test was carried out at three different sites (near Kharagpur City, India) on Kasai river bed and in its close proximity in order to design subsurface RC well for water supply to Kharagpur City. The appropriate hydrological approaches were employed to estimate values of aquifer parameters, viz. storage coefficient (S) and coefficient of transmissibility (T) for the aforesaid sites under study, which were found to be in the ranges of 0.00129-0.068 and 810-2573 m3/day-m, respectively. This article reports the rationality of design methods of sub-surface RC well, based on image theory and model study, which was adequately supported with geophysical investigations. An RC well-system was designed following the aforesaid two methods and was constructed at the proposed Site-II, which was found to be the most favourable one based on remote sensing survey, geophysical studies, and hydrological investigations. In the trial operating stage of the RC well, commissioned at Site II, the observed yield was compared with the designed (predicted) values. Trial field (yield) test data at Site II showed that the designed yield of 24 million litres per day (MLD) based on model study was closer to field data (21 MLD) than that (8 MLD) obtained based on image theory. © Springer-Verlag 2011.